The Patient Activation Measure (PAM) and the pandemic: Predictors of patient activation among Australian health consumers during the COVID‐19 pandemic - Genevieve Dammery; Kathryn Vitangcol; James Ansell; Louise A. Ellis; Carolynn L. Smith; Ann Carrigan; Jeffrey Braithwaite; Yvonne Zurynski (Wiley, 2023)
Abstract Background Preventative healthcare is crucial for improving individual patient outcomes and is integral to sustainable health systems. The effectiveness of prevention programs is enhanced by activated populations who are capable of managing their own health and are proactive to keep themselves well. However, little is known about the level of activation among people drawn from general populations. We used the Patient Activation Measure (PAM) to address this knowledge gap. Methods A representative, population‐based survey of Australian adults was conducted in October 2021 during the Delta strain outbreak of the COVID‐19 pandemic. Comprehensive demographic information was collected, and the participants completed the Kessler‐6 psychological distress scale (K6) and PAM. Multinomial and binomial logistic regression analyses were performed to determine the effect of demographic factors on PAM scores, which are categorised into four levels: 1-participants disengaged with their health; 2-becoming aware of how to manage their health; 3-acting on their health; and 4-engaging with preventative healthcare and advocating for themselves. Results Of 5100 participants, 7.8% scored at PAM level 1; 13.7% level 2, 45.3% level 3, and 33.2% level 4. The mean score was 66.1, corresponding to PAM level 3. More than half of the participants (59.2%) reported having one or more chronic conditions. Respondents aged 18 to 24 years old were twice as likely to score PAM level 1 compared with people aged 25-44 (p < .001) or people aged over 65 years (p < .05). Speaking a language other than English at home was significantly associated with having low PAM (p < .05). Greater psychological distress scores (K6) were significantly predictive of low PAM scores (p < .001). Conclusion Overall, Australian adults showed high levels of patient activation in 2021. People with lower incomes, of younger age, and those experiencing psychological distress were more likely to have low activation. Understanding the level of activation enables targeting sociodemographic groups for extra support to increase the capacity to engage in prevention activities. Conducted during the COVID‐19 pandemic, our study provides a baseline for comparison as we move out of the pandemic and associated restrictions and lockdowns. Patient or Public Contribution The study and survey questions were co‐designed with consumer researchers from the Consumers Health Forum of Australia (CHF) as equal partners. Researchers from CHF were involved in the analysis of data and production of all publications using data from the consumer sentiment survey.